PERTANGGUNGJAWABAN PIDANA TERHADAP PEMILIK DOMAIN CYBERPORN BERDASARKAN UNDANG UNDANG NOMOR 44 TAHUN 2008 TENTANG PORNOGRAFI - Ibnu Ricki Rezky; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Talking about the crime of pornography can not be separated from criminal liability. Domains are still accessible and also provide blocking pornography and should be held accountable to the domain owner. Because the owner of the domain can be categorized as pornography providers in offering services based on Article 4 of Law No. 44 Year 2008 on Pornography.